Development of Digital Flipbook-based History Learning Media to Overcome High School Students' Learning Loss - Lubis, Hafnita Sari Dewi; Tanjung, Yushar; Nasution, M. Ihsan Syahaf; Nasution, Ahmad Arif Budiman; Tannoubi, Amayra (Jurnal Ilmu Pendidikan, 2023)
This research aims to develop interactive learning media, especially digital flipbooks, to overcome learning loss in history learning. The research method involves the stages of needs analysis, design creation, media development, media testing, and evaluating its impact on student understanding. The research subjects in this study consisted of 12 expert validators with 3 experts each for each aspect. Expert validators are selected based on their expertise in the fields of learning, historical materials, media and language. Apart from that, this research also involved 50 Pertiwi Medan Private High School students who were randomly selected to assess the media produced. Data was collected by interviews and distributing questionnaires. Data analysis involves comparing test results using paired t-tests. The research results show that the digital flipbook media developed is valid for use in overcoming learning loss. The t test results show a significance value of 0.000, which means there is a difference in scores before and after using digital flipbook media. The conclusion of this research shows that the development of digital flipbook learning media has great potential in overcoming learning loss in history learning and has a significant positive impact on student learning outcomes.Keywords: Digital flipbook, Learning Loss, History Learning.